Weekend Tourism - a Tourism Product aimed at Customers Living and Working in Big Cities in Vietnam - Xuan Thi Hong Phan (Program MM Universitas Surabaya, 2020)
To implement this article, we have chosen the research area of Binh Duong (bordering Ho Chi Minh City, with a history of over 300 years of development, with 11 years of operating the type of weekend tourism from 2008 to present); have used some research methods in social sciences, particularly ethnographic fieldwork such as strategic interview, comparing and analyzing data gathered from multiple sources. The article consists of three parts: The concept of